The Impact of R&D Investment on The Financialization of Enterprises —— Take The Manufacturing Industry as An Example - Xu, Qingyu (Transactions on Economics, Business and Management Research, 2024)
In recent years, the excessive investment of entity enterprises leads to the phenomenon of enterprise financialization, which makes the development of entity enterprises fall into a vicious circle. How to restrain the excessive financialization trend of enterprises and promote the high-quality development of real enterprises has become an urgent problem to be solved. Based on the financial data of listed companies in A-share manufacturing industry from 2008 to 2022, this paper studies the possible inhibitory effect of enterprise R&D investment on finalized investment from the perspective of asset allocation and market competition. The results show that R&D investment is significantly negatively correlated with the level of enterprise financialization, that is, R&D investment can restrain enterprise financialization to a certain extent. Further research shows that increasing cash holding and increasing market power are two intermediary paths for R&D investment to restrain the financialization of enterprises.